2021
DOI: 10.1186/s13195-020-00752-w
|View full text |Cite
|
Sign up to set email alerts
|

Distinct network topology in Alzheimer’s disease and behavioral variant frontotemporal dementia

Abstract: Background Alzheimer’s disease (AD) and behavioral variant frontotemporal dementia (bvFTD) cause distinct atrophy and functional disruptions within two major intrinsic brain networks, namely the default network and the salience network, respectively. It remains unclear if inter-network relationships and whole-brain network topology are also altered and underpin cognitive and social–emotional functional deficits. Methods In total, 111 participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 116 publications
6
45
0
1
Order By: Relevance
“…It's worth noting that the potential effect of rTMS spread from directly targeted areas to anatomically areas, which provides an opportunity to apply rTMS at one point of neural circuit [54]. And, previous graph theoretical analysis in functional network showed that AD patients had higher degree centrality and nodal e ciency in thalamus [34]. These ndings were consistent to our results.…”
Section: The Underlying Mechanism and Intervention Opportunity Of Cognitive Improvementsupporting
confidence: 91%
See 1 more Smart Citation
“…It's worth noting that the potential effect of rTMS spread from directly targeted areas to anatomically areas, which provides an opportunity to apply rTMS at one point of neural circuit [54]. And, previous graph theoretical analysis in functional network showed that AD patients had higher degree centrality and nodal e ciency in thalamus [34]. These ndings were consistent to our results.…”
Section: The Underlying Mechanism and Intervention Opportunity Of Cognitive Improvementsupporting
confidence: 91%
“…(i) Post-wise differences correlation: It should be noted that the improved white matter integrity of right Thalamic Radiation were observed after four-week neuro-navigated rTMS treatment. Among MCI group, the increased white matter integrity of posterior portion of the right Thalamic Radiation's (nodes 88-94) correlated positively with the improved episodic memory (r = 0.585, p = 0.028) and improved language function (r = 0.663, p = 0.007) (ii) Theoretical parameter correlation: previous studies demonstrated that compared to healthy control, AD patients showed higher degree centrality and nodal e ciency in thalamus [34]. We thought that network attributes of the thalamus were improved after the intervention.…”
Section: The Changed Diffusion Metrics Theoretical Parameter and Behavioral Signi Cancementioning
confidence: 91%
“…Following the similar approach of segregation calculation as in our work, recent studies showed significant reduced segregations in the global system and the episodic memory networks in patients with AD ( Cassady et al, 2021 , Ewers et al, 2021 ). Using various other measures of segregation such as clustering coefficient or within-module degree, decreased segregation has been reported in the whole brain and multiple networks in patients with MCI and AD ( Brier et al, 2014 , Contreras et al, 2019 , Costumero et al, 2020 , Dai et al, 2019 , Ng et al, 2021 , Tumati et al, 2020 ). Together, these results indicate that the distinct and functionally specialized role of individual network seemed to be blurred in the brain functional organization of MCI and AD.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies have applied advanced MRI acquisitions and analyses to obtain an in-depth characterization of brain alterations with respect to the simple gray matter atrophy. Particularly, an increasing number of studies have assessed brain connectivity through graph-theoretical methods, highlighting that this approach shows unique potentialities in FTD (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%